ANALISIS STRATEGI PADA UMKM KAMSIA BOBA TERHADAP PENJUALAN YANG MODERN - Putri Octavia Maharani; Tyna Yunita; Muhammad Dzaky; Novia Hanifah Rahma (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The Kamsia Boba business was established with the aim of fulfilling people's demand for boba drinks which are currently popular. Boba is a tapioca ball that is often used as a filling for bubble tea drinks. To achieve its vision and mission, Kamsia Boba needs the right strategy to increase sales and compete with other boba drink manufacturing companies that have already entered the market. The purpose of this research is to analyze the strategy used by Kamsia Boba in increasing sales through the use of modern technology. The research method used is a qualitative method with interview and observation techniques. Sources of data used are primary data and secondary data. The final result of the research is that there are several strategies used while running the